Performance of sustainable concrete containing recycled latex gloves and silicone catheter under elevated temperature - Al Biajawi, Mohammad Ismail Yousef; Wahppe Alkasawneh, Rufaidah; Mostafa, Sahar A.; Izwan, Johari; Rahimah, Embong; Khairunisa, Muthusamy (King Saud University, 2021)
Due to its environmental, economic, and durability advantages, sustainable concrete has considerably increased the potential of research in recent years. This paper investigates how rubber waste affects the mechanical properties, durability, and microstructure of the concrete matrix. Industrial rubber such as ground latex gloves (LG) and silicone catheters (SC) are substituted for coarse aggregate in concrete mixes. Workability, density, compressive strength, water absorption, ultrasonic pulse velocity, and scanning electron microscope (SEM) tests are applied to examine the performance and properties of the modified concrete. The impact of high temperatures on concrete containing industrial rubber is also examined. To achieve this objective, the samples are tested at normal and high temperatures (room temperature, 200 °C, and 400 °C, respectively) and four substitution levels are used (2.5%, 5%, 7.5%, and 10%) by weight. The results illustrate that the inclusion of different percentages of the LG and SC significantly improves the water absorption of the concrete samples. In addition, the density of concrete containing recycled rubber decreases by 34%. Compressive strength decreased by 86% and 59% at a replacement level of 10% for LG and SC, respectively. High-temperature level has shown a significant effect on the properties of rubberized concrete. This study establishes the possibility of incorporating LG and SC at limited replacement levels in concrete; thereby, proving that these materials are applicable in industrial use.